Design and fabrication of automatic can crusher / Muqri Azfar Mohd Faizar and Radzi Abdul Rasih - Mohd Faizar, Muqri Azfar; Abdul Rasih, Radzi (School of Mechanical Engineering, 2023)
Can crushers have been in use for a considerable period, and numerous designs and fabrication methods have been developed over time. This project aims to introduce a new concept of an automatic can crusher capable of crushing two cans simultaneously. Placing one can after another in the machine for crushing can be hazardous for the hands, requiring precise timing. This poses a risk of injury and increases the time required for compression. In this project, the cans are arranged horizontally in a slider and compressed in sequence. An automatic pneumatic piston will crush the cans when users press a button. Once compressed, the cans will fall into a collection box. This machine will significantly reduce the time required for compression and offer a more affordable option compared to market prices.